2016
DOI: 10.15302/j-fase-2016090
|View full text |Cite
|
Sign up to set email alerts
|

Improving water use efficiency in grain production of winter wheat and summer maize in the North China Plain: a review

Abstract: Reducing irrigation water use by improving water use efficiency (WUE) in grain production is critical for the development of sustainable agriculture in the North China Plain (NCP). This article summarizes the research progresses in WUE improvement carried out at the Luancheng station located in the Northern part of NCP for the past three decades. Progresses in four aspects of yield and WUE improvement are presented, including yield and WUE improvement associated with cultivar selection, irrigation management f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…Ancient varieties tented to have lower WUE GY (5.5 kg ha -1 mm -1 ) than newly realized ones (7.0 kg ha -1 mm -1 ), while no clear differences appeared for WUE TDM (21.4 kg ha -1 mm -1 vs 20.8 kg ha -1 mm -1 , respectively). These supported results reported by Zhang et al, (2016) whom carried out studies to understand the genetic gains in yield and WUE and their associated physiologic and agronomic traits for winter wheat and found that WUE increased substantially from 1.0 to 1.2 kg m -3 for cultivars from the early 1970s to 1.4-1.5 kg m -3 for recently released cultivars. Genotypic differences in WUE GY were also reported by van den Boogaard et al (1997), andZhang et al (2010).…”
Section: Water Use Efficiencysupporting
confidence: 86%
See 1 more Smart Citation
“…Ancient varieties tented to have lower WUE GY (5.5 kg ha -1 mm -1 ) than newly realized ones (7.0 kg ha -1 mm -1 ), while no clear differences appeared for WUE TDM (21.4 kg ha -1 mm -1 vs 20.8 kg ha -1 mm -1 , respectively). These supported results reported by Zhang et al, (2016) whom carried out studies to understand the genetic gains in yield and WUE and their associated physiologic and agronomic traits for winter wheat and found that WUE increased substantially from 1.0 to 1.2 kg m -3 for cultivars from the early 1970s to 1.4-1.5 kg m -3 for recently released cultivars. Genotypic differences in WUE GY were also reported by van den Boogaard et al (1997), andZhang et al (2010).…”
Section: Water Use Efficiencysupporting
confidence: 86%
“…These traits appeared to be useful for WUE GY improvement (Table 6). In this context, Zhang et al, (2016) found no significant correlations between WUE GY and LCHC, or LRWC, but significant correlations were found between WUE GY and HI. Through multiple regression analysis Atta (2013) identified several key traits that contribute to improve WUE among which leaf traits, plant height, total dry matter at maturity, harvest index and grain yield which corroborated partially the results of this study.…”
Section: Relationships Between Wue and The Physio-agronomic Traitscontrasting
confidence: 58%
“…However, in addition to the influence of irrigation, other anthropogenic activities, such as changing the amount of fertilizer applied and renewing plant varieties, also greatly affect the changes in GPP for each irrigated district. Previous studies in the NCP have proved this [98,99]. As a result, GPP showed stronger variability in years with both large (2011 and 2015) and small (2010 and 2013) ET seasonal changes among the 12 irrigation districts.…”
Section: Variations In Monthly Et Gpp and Wue For 12 Irrigation Districtsmentioning
confidence: 71%
“…High losses tend to occur at the beginning of N fertilizer applications through volatilization, denitrification, or leaching [ 5 ]. Maize yield is highly affected by crop agronomic management, and water use efficiency and fertilization are the most important variables [ 11 , 12 ]. In fact, one of the most relevant environmental problems in maize cultivation is caused by eutrophication polluting aquifers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%